Achieving high efficient gasoline compression ignition (GCI) combustion through the cooperative-control of fuel octane number and air intake conditions. (15th April 2019) - Jiang, Chenxu; Li, Zilong; Liu, Guibin; Qian, Yong; Lu, Xingcai
Highlights: Intake conditions and fuel octane number have significant influences on GCI combustion and emissions. Intake heating significantly improve the engine performance and emissions under low loads. Using PRF70 with supercharging obtained the indicated thermal efficiency of over 47% under medium loads. Abstract: Gasoline compression ignition (GCI) is a promising advanced combustion mode to improve the fuel economy and reduce emissions. The intake conditions have significant effects on GCI combustion. To explore the proper intake conditions and fuels to achieve high efficiency under all loads, several experimental tests were carried out to investigate the effects of intake pressure and intake temperature on GCI combustion and emissions in this paper. Four primary reference fuels (PRF) with the research octane number (RON) of 90, 80, 70 and 60 were applied in this paper, which are recorded as PRF90, PRF80, PRF70 and PRF60. The results show that high efficiency under all loads could be achieved indeed by choosing proper intake pressure, intake temperature and fuels. The increase in intake pressure could significantly improve the fuel economy and decrease the CO, THC and NOx emissions. The increase in intake temperature increased the thermal efficiency under low loads and decreased the CO and THC emissions, but increased the NOx emissions simultaneously. However, with the increase in loads, the increased intake temperature reduced the volumetric efficiency, thus worsening the fuel economy. In addition, the influence of intake temperature on GCI combustion decreased with the decrease in RON. In general, high efficiency could be achieved by applying PRF70 and intake heating under low loads, as well as PRF70 under medium loads and PRF90 under high loads without intake heating, combined with supercharge under all loads. The highest indicated thermal efficiency (ITE) could reach 47% with PRF70 under medium loads.